ANALISIS DAN PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS RADIO DAN TELEVISI SIARAN PROPINSI JAMBI BERBASIS WEB PADA BALAI MONITOR SFR JAMBI - Bawono, Bimo Adi; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2019)
The problems that faced by Balai Monitor SFR Kelas II Jambi Office is they have difficulty inlocating, identifying and analyzing of radio frequency interference in radio and televisionbroadcasting. This problem caused by their radio and television broadcasting data still on excelform and not yet available a georgraphic information system which show the location andtechnical data of the radio and television broadcast. The aims of this study are to analyze theneeds of geographic information system required by Balai Monitor SFR Kelas II Jambi Office,then design it using UML (Unifed Modeling Language) and develop it in the form of geographicinformation system webisite using php, maria db, and google map api application. The result ofthis study is a web-based geographic information system for broadcasting radio and televisionin Jambi Province, with location search, identification and analysis of frequency interferencefeatures that have been successfully tested, so it can be used to deal with problems that havebeen faced by Balai Monitor SFR Kelas II Jambi Office